2003
DOI: 10.1007/s00442-003-1358-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance of a tropical savanna of northern Australia

Abstract: Through estimations of above- and below-ground standing biomass, annual biomass increment, fine root production and turnover, litterfall, canopy respiration and total soil CO(2) efflux, a carbon balance on seasonal and yearly time-scales is developed for a Eucalypt open-forest savanna in northern Australia. This carbon balance is compared to estimates of carbon fluxes derived from eddy covariance measurements conducted at the same site. The total carbon (C) stock of the savanna was 204+/-53 ton C ha(-1), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
140
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 49 publications
20
140
4
Order By: Relevance
“…However, such estimate was higher than that obtained for a similar forest in the Hunan province (3.96 t C ha -1 y -1 -Xiao et al 2010), as well as for an open eucalypt savanna in northern Australia (3.8 t C ha -1 y -1 - Chen et al 2003). Contrastingly, annual NEP estimated in this study was lower than that reported for a European temperate deciduous forest (5.9 t C ha -1 y -1 - Malhi et al 1999) and a natural evergreen forest of Castanopsis kawakamii (7.5 t C ha -1 y -1…”
Section: Carbon Balancementioning
confidence: 61%
“…However, such estimate was higher than that obtained for a similar forest in the Hunan province (3.96 t C ha -1 y -1 -Xiao et al 2010), as well as for an open eucalypt savanna in northern Australia (3.8 t C ha -1 y -1 - Chen et al 2003). Contrastingly, annual NEP estimated in this study was lower than that reported for a European temperate deciduous forest (5.9 t C ha -1 y -1 - Malhi et al 1999) and a natural evergreen forest of Castanopsis kawakamii (7.5 t C ha -1 y -1…”
Section: Carbon Balancementioning
confidence: 61%
“…) [64], while in South and Central America, the highest biomass values recorded have been observed in Brazilian cerrado vegetation (~31.8 tha −1 ) [65]. This leads to the suggestion that the pantropical carbon maps may be overestimating AGWB in savanna areas, and this suggestion will need to be explored more rigorously as more field-based estimates of biomass are collated from other savanna woodlands.…”
Section: Figurementioning
confidence: 99%
“…Chen et al 2003;Williams et al 2004Williams et al , 2005 suggest that for the Eucalyptus miniata-tetrodonta savannas, which are very extensive in the higher rainfall areas of Northern Australia, more carbon is sequestered than lost back to the atmosphere, with this amount increasing when fires are less frequent, intense or extensive. That is, these savannas are carbon sinks.…”
Section: Living In the Landmentioning
confidence: 99%